Racial extinction and regeneration: representation of North Africa in the factual and fictional writings of Grant Allen - Mohd Ramli, Aimillia (2015)
Today Grant Allen is known chiefly for two things: first, as an evolutionist, and second, as the best-selling writer of the “New Women” novel The Woman Who Did (1895). What remains less well-known are his writings that incorporate evolutionary theory with a major motif in late nineteenth-century English literature, namely a desire to feature the racial “other” within the European worldview. The objective of this paper is to explore his depictions of North Africans in light of his engagement with issues connected to late nineteenth-century racial discourse: degeneration, extinction and regeneration. It highlights his contributions to the racial discourse circulating throughout the nineteenth century with regards to the Kabyles, a sub-division of the Berbers, as the long-lost descendants of the Romans who had formerly conquered North Africa.